2007
DOI: 10.1295/koron.64.223
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Metal-Ion-Capturing Function of Amidinourea Resins

Abstract: The substituent effects on the metal-ion-capturing function of amidinourea resins were investigated. The metal-ion-capturing function likely depends on the steric effects and/or hydrophilic/hydrophobic properties of the three substituents around the capturing sites. In order to clarify these points, we synthesized eight amidinourea resins having acyclic-and cyclic substituents with various numbers of carbon atoms. The adsorption analysis and the water-solubility test indicated that the hydrophilic/hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Although substitution by alkyl and benzyl groups (resins 1–6) leads to a decrease in the adsorption efficiency because of the corresponding steric hindrance and hydrophobic regions, substitution by pyrrolidil and piperidil groups (resin 7 and 8) leads to an increase in the adsorption efficiency, in which the spread of hydrophilic region overcomes the steric‐hindrance effects. Moreover, it was found that the adsorption efficiency was approximately proportional to the water solubility of the corresponding substituted amidinoureas . These facts show that boundary films are formed at the surface of resins, and the importance of film diffusion in polymer complexes is implied.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Although substitution by alkyl and benzyl groups (resins 1–6) leads to a decrease in the adsorption efficiency because of the corresponding steric hindrance and hydrophobic regions, substitution by pyrrolidil and piperidil groups (resin 7 and 8) leads to an increase in the adsorption efficiency, in which the spread of hydrophilic region overcomes the steric‐hindrance effects. Moreover, it was found that the adsorption efficiency was approximately proportional to the water solubility of the corresponding substituted amidinoureas . These facts show that boundary films are formed at the surface of resins, and the importance of film diffusion in polymer complexes is implied.…”
Section: Introductionmentioning
confidence: 84%
“…As introduced previously, the adsorption efficiencies of ion‐exchange resins are highly dependent on the hydrophilic and hydrophobic properties of substituents around the ligands . Moreover, the adsorption efficiencies are also affected by the polarization of the polymer chain .…”
Section: Effects Of the Boundary Filmmentioning
confidence: 89%
See 3 more Smart Citations